Comparison of Microsampling and Conventional Sampling Techniques for Quantification of Warfarin in Blood Samples: A Systematic Review (Sciences of Pharmacy, 2023)
Warfarin is a vitamin K antagonist (VKAs) anticoagulant associated with interindividual patients’ response to therapy, narrow therapeutic index, and serious adverse drug events. Monitoring ensures efficacy and safety by measuring drug concentration in the bloodstream, which demands blood or plasma samples from patients through conventional sampling. Conventional sampling often requires invasive methods that may be uncomfortable for patients. Microsampling offers an opportunity to reduce the burden of multiple blood sampling on patients and simplifies the process of sample transportation and storage. This systematic review describes conventional and microsampling techniques for quantifying warfarin in human blood samples and the bioanalytical method employed to perform the analysis. Related studies (537) were screened from several databases and narrowed down into 12 eligible articles, which were then used to fulfill the purpose of this review in a narrative form. It is concluded that while there are still limited studies regarding the application of microsampling for warfarin quantification in patients, there has been evidence of comparable plasma and micro samples results, highlighting the potential for future development of routine monitoring using the microsampling technique.